Training-related modulations of the autonomic nervous system in endurance athletes: is female gender cardioprotective? - Fürholz, M.; Radtke, T.; Roten, L.; Tanner, H.; Wilhelm, I.; Schmid, J. P.; Saner, H.; Wilhelm, M. (European Journal of Applied Physiology, 2013)
The risk of sudden death is increased in athletes with a male predominance. Regular physical activity increases vagal tone, and may protect against exercise-induced ventricular arrhythmias. We investigated training-related modulations of the autonomic nervous system in female and male endurance athletes. Runners of a 10-mile race were invited. Of 873 applicants, 68 female and 70 male athletes were randomly selected and stratified according to their average weekly training hours in a low (<4 h) and high (>4 h) volume training group. Analysis of heart rate variability was performed over 24 h. Spectral components (high frequency [HF] and low frequency [LF] power in normalized units) were analyzed for hourly 5 min segments and averaged for day- and nighttime. One hundred and fourteen athletes (50 % female, mean age 42 ± 7 years) were included. No significant gender difference was observed for training volume and 10-mile race time. Over the 24-h period, female athletes exhibited a higher HF and lower LF power for each hourly time-point. Female gender and endurance training hours were independent predictors of a higher HF and lower LF power. In female athletes, higher training hours were associated with a higher HF and lower LF power during nighttime. In male athletes, the same was true during daytime. In conclusion, female and male athletes showed a different circadian pattern of the training-related increase in markers of vagal tone. For a comparable amount of training volume, female athletes maintained their higher markers of vagal tone, possibly indicating a superior protection against exercise-induced ventricular arrhythmias.